Developing a semantic service transaction system in the DE environment - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Digital Ecosystem (DE), which is an emerging service environment beyond the service-oriented architecture (SOA), is increasingly attracting researchers? interest. However, current literature reveals that there is not reliable and trustworthy technical support for service transaction activities in the DEenvironment. In this paper, we propose a semantic service transaction system ? SST, in order to provide the reliable and trustworthy services in the aspects of service search, negotiation, contract and feedback.